Pendampingan Menulis Puisi Metode Think-Pair-Share pada Siswa sebagai Penguatan Pendidikan Karakter - Ulwatunnisa, Marwah; Arifin, Syaiful; Indrahastuti, Tri (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
The aim of this community service activity is to provide education and learning to the students of SMAN 5 Samarinda, in order to enhance their writing skills and character education using the Think-Pair-Share method. This activity is particularly beneficial in developing potential and interest in literary works. The implementation of this PKM involves three stages: preparation, activity execution, and report preparation. During the execution phase, participants will be provided with materials on poetry, the building blocks or structure of poetry, and poetry writing techniques. The Think-Pair-Share method will then be applied as follows: Think; participants discuss the task in groups, Pair; participants work in groups to complete the task, and Share; participants present their group's writing results and listen to the opinions of other groups. Finally, participants will practice independently in groups under guidance to produce literary works, specifically poetry.